The Face‐Value Theory, Know‐that, Know‐wh and Know‐how. (6th February 2019) - Felappi, Giulia
Abstract : For sentences such as (1) Columbus knows that the sea is unpredictable there is a face‐value theory, according to which 'that'‐clauses are singular terms denoting propositions. Famously, Prior raised an objection to the theory, but defenders of the face‐value theory such as Forbes, King, Künne, Pietroski and Stanley urged that the objection could be met by maintaining that in (1) 'to know' designates a complex relation along the lines of being in a state of knowledge having as content . Is the theory safe, then? The aim of this paper is to show that a new problem for the theory arises if we consider some clauses other than 'that'‐clauses.